2014
DOI: 10.1371/journal.pone.0106487
|View full text |Cite|
|
Sign up to set email alerts
|

High Density Lipoprotein Stimulated Migration of Macrophages Depends on the Scavenger Receptor Class B, Type I, PDZK1 and Akt1 and Is Blocked by Sphingosine 1 Phosphate Receptor Antagonists

Abstract: HDL carries biologically active lipids such as sphingosine-1-phosphate (S1P) and stimulates a variety of cell signaling pathways in diverse cell types, which may contribute to its ability to protect against atherosclerosis. HDL and sphingosine-1-phosphate receptor agonists, FTY720 and SEW2871 triggered macrophage migration. HDL-, but not FTY720-stimulated migration was inhibited by an antibody against the HDL receptor, SR-BI, and an inhibitor of SR-BI mediated lipid transfer. HDL and FTY720-stimulated migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 131 publications
3
50
0
Order By: Relevance
“…For example, oxLDL inhibits macrophage migration by promoting macrophage trapping , a process that helps mediate foam cell formation and pro‐inflammatory signaling. On the other hand, HDL promotes the migration of macrophages through an SR‐BI–dependent process . Therefore, we performed a Boyden Chamber assay to determine the impact of aldehyde modification on HDL’s ability to promote macrophage migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, oxLDL inhibits macrophage migration by promoting macrophage trapping , a process that helps mediate foam cell formation and pro‐inflammatory signaling. On the other hand, HDL promotes the migration of macrophages through an SR‐BI–dependent process . Therefore, we performed a Boyden Chamber assay to determine the impact of aldehyde modification on HDL’s ability to promote macrophage migration.…”
Section: Resultsmentioning
confidence: 99%
“…In macrophages, HDL also protects against the generation of ROS and promotes the production of anti‐inflammatory cytokines . Furthermore, by interacting with SR‐BI, HDL can promote macrophage migration and prevent foam cell formation (reviewed in ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PI3K/Akt signaling in macrophages regulates NF-κB activation (Figure 3)[76, 79], and recent studies have shown that the interaction of macrophage SR-BI with apoptotic cells activates PI3K/Akt signaling (Figure 3) and induces expression of anti-inflammatory cytokines(Il-10, TGF-β)[11]. In addition, HDL activates PI3K/Akt signaling in macrophages, which is mediated by SR-BI and involves interaction with its adaptor protein, PDZK1(Box 1), and activation of S1P receptor 1(S1PR1) signaling[40]. Thus, a likely mechanism by which SR-BI regulates inflammation is by activating Akt phosphorylation leading to reduced NF-κB activation (Figure 3)[40].…”
Section: Role Of Sr-bi Signaling In Preventing Inflammation and Athermentioning
confidence: 99%
“…In addition, HDL activates PI3K/Akt signaling in macrophages, which is mediated by SR-BI and involves interaction with its adaptor protein, PDZK1(Box 1), and activation of S1P receptor 1(S1PR1) signaling[40]. Thus, a likely mechanism by which SR-BI regulates inflammation is by activating Akt phosphorylation leading to reduced NF-κB activation (Figure 3)[40]. …”
Section: Role Of Sr-bi Signaling In Preventing Inflammation and Athermentioning
confidence: 99%
See 1 more Smart Citation